Preliminary Characterization and Consumer Insights of Juice Enzymatically Extracted from North American Pawpaw (Asimina triloba) - Robert G. Brannan (Beverages, 2025)
This study reports for the first time parameters and consumer preferences about juice prepared from North American pawpaw fruit (Asimina triloba). Enzymatic extraction using a commercial preparation of pectinases, hemicellulases, and beta-glucanases (Pectinex® Ultra SP-L) significantly increased juice yield compared to non-enzyme extraction, but enzyme concentration (0.05% vs. 0.1%) and acidification method (citric vs. tartaric acid) showed no significant differences. Sensory panelists found no significant differences between citric and tartaric acid acidified juices, or between juices prepared from fresh pawpaw and pawpaw stored refrigerated for 14 days. Blending pawpaw juice with fruit juices improved overall acceptability compared to blending with fruit purees. Consumer testing revealed no overall preference among five juice formulations (100% pawpaw juice, sweetened pawpaw juice, pawpaw juice with the addition of 10% apple, orange, or pineapple juice). Consumers highlighted the complex flavor profile of pawpaw, with sweet and bitter tastes, and melon, papaya, and pear flavors being most frequently identified. Sweetening the juice altered the flavor profile, masking sourness and certain flavors. Based on this preliminary study, challenges and opportunities were identified for the development of a pawpaw-based juice.